Venus in Fur:: analysis of an artistic work in theater and cinema in the light of great time - Zanato de Carvalho Ribeiro, João Vítor; Balieiro Lodi, Ana Claudia (Revista Brasileira de Estudos da Presença, 2025)
This article aims to analyze the artistic work Venus in Fur through the theatrical play Venus in Fur, written by David Ives in 2010, and the French feature film Venus in Fur, directed by Roman Polanski in 2013. In this analysis, we seek to understand the dialogues established between the play and the film with previous artistic works, involving the historically built meanings about women and their social role, themes that permeate Venus in Fur. The theoretical-methodological perspective that underpins the proposed analysis is based on the studies of Bakhtin and the Bakhtin Circle, by understanding that artistic works are part of a long human discursive chain of great time, reflecting and refracting their own time, while responding to the past and being projected into the future. In turn, Venus in Fur promotes a major feast of renewal of meanings, extending its dialogue beyond its socio-historical context of circulation, reaching works from the past and other contexts, by situating the representation of women in art at the center of its discussion.